2021
DOI: 10.1177/1708538121996573
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ankle-brachial index and thermography measurements in patients with peripheral arterial disease

Abstract: Objectives To correlate the ankle-brachial index and photographic thermography findings in patients with peripheral arterial disease. Methods Photographic thermography was performed at the foot level, and ankle-brachial index was measured in 72 lower limbs of 53 patients with peripheral arterial disease who were divided into calcified artery, patients with an ankle-brachial index greater than 1.4; and non-calcified artery classified as asymptomatic, mild, moderate, and severe on the basis of peripheral arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The included studies reported different measurement sites, focusing in particular on the feet. One study did not precisely describe the measurement location [ 45 ], 2 articles studied the ankle and the anterior tibial face [ 39 , 44 ], six the toes [ 2 , 32 , 33 , 41 , 42 , 43 , 48 ], seven the dorsum of the foot [ 31 , 32 , 37 , 38 , 39 , 46 , 49 ] and eleven authors identified the plantar side of the foot, making it the most studied area [ 22 , 32 , 33 , 34 , 35 , 36 , 40 , 42 , 44 , 50 ]. A summary of the measurement locations is reported in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies reported different measurement sites, focusing in particular on the feet. One study did not precisely describe the measurement location [ 45 ], 2 articles studied the ankle and the anterior tibial face [ 39 , 44 ], six the toes [ 2 , 32 , 33 , 41 , 42 , 43 , 48 ], seven the dorsum of the foot [ 31 , 32 , 37 , 38 , 39 , 46 , 49 ] and eleven authors identified the plantar side of the foot, making it the most studied area [ 22 , 32 , 33 , 34 , 35 , 36 , 40 , 42 , 44 , 50 ]. A summary of the measurement locations is reported in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The study of de Carvalho Abreu et al [ 22 ] correlated IRT findings and ABI in patients with PAD and observed a strong direct correlation between IRT and ABI in patients with noncalcified arteries. Moreover, the study of Wallace et al [ 37 ] found a positive correlation, concluding that IRT is a valid method in addition to ABI to assess PAD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations